1st International Conference in Applied Physics and Materials Science. Issue 1 (10th June 2015) - Unknown
Abstract : We are delighted to come up with thirty two (32) contributed research papers in these proceedings, focusing on Materials Science and Applied Physics as an output of the2013 International Conference in Applied Physics and Materials Science (ICAMS2013) held on October 22-24, 2013 at the Ateneo de Davao University, Davao City, Philippines. The conference was set to provide a high level of international forum and had brought together leading academic scientists, industry professionals, researchers and scholars from universities, industries and government agencies who have shared their experiences, research results and discussed the practical challenges encountered and the solutions adopted as well as the advances in the fields of Applied Physics and Materials Science. This conference has provided a wide opportunity to establish multidisciplinary collaborations with local and foreign experts. ICAMS2013, held concurrently with15th Samahang Pisika ng Visayas at Mindanao (SPVM) National Physics Conference and2013 International Meeting for Complex Systems, was organized by the Samahang Pisika ng Visayas at Mindanao (Physics Society of Visayas and Mindanao) based in MSU-Iligan Institute of Technology, Iligan City, Philippines. The international flavor of converging budding researchers and experts on Materials Science and Applied Physics was the first to be organized in the 19 years of SPVM operation in the Philippines. We highlighted ICAMS2013 gathering by the motivating presence of Dr. Stuart Parkin, a British Physicist, as one of our conference's plenary speakers. Equal measures of gratitude were also due to all other plenary speakers, Dr. Elizabeth Taylor of Institute of Physics (IOP) in London, Dr. Surya Raghu of Advanced Fluidics in Maryland, USA and Prof. Hitoshi Miyata of Niigata University, Japan, Prof. Djulia Onggo of Institut Teknologi Bandung, Indonesia, and Dr. Hironori Katagiri of Nagaoka National College of Technology, Japan. The warm hospitality of the host university, Ateneo de Davao University, Davao City, Philippines blended with the overwhelming enthusiasm of the conference speakers, participants, and the unwavering support of the conference sponsors and donors and the administration of the MSU-Iligan Institute of Technology, Iligan City, Philippines, all have brought realization to the production of these proceedings.